Efektivitas Program Mahasiswa Wirausaha (PMW) dalam Meningkatkan Kemampuan Berwirausaha Mahasiswa Universitas Halu Oleo (UHO) - Aulia, La Ode Afridin; Rianse, Usman; Abdullah, Weka Gusmiarty (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
The purpose of this research was the perceptions of Entrepreneurial Student Program at the Universitas Halu Oleo (UHO) and effectiveness of the programme in improving the Entrepreneurial ability of Student entrepreneurship students. The population in this research was all the UHO Student get Entrepreneurial Student Program and has undergone such business in the field of agribusiness which totaled 54 people, which was then as a census so that respondents in this research totalled 54 respondents. The analysis of the data used, namely the analysis of Interval Classes with the help of the program SPSS. The results showed that Students Entrepreneurial Program at the Universitas Halu Oleo (UHO) fairly well implemented, This was apparent from consisted of indicators Entrepreneurial Student Program entirely situated on the category was being i.e. the mean 75,00 %. The effectiveness of the Entrepreneurial Students Program in the Universitas Halu Oleo (UHO) in Self-employment entrepreneurship capabilities of students quite effective It can be seen from all the indicators of effectiveness PMW located on the composition of the was being the mean 69 %.